2017
DOI: 10.1101/116996
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Molecular basis underlying male sterility in bHLH142 overexpressing rice

Abstract: Development of stable male sterility lines is essential for efficient hybrid seed production. We previously showed that knockout of bHLH142 in rice (Oryza sativa) causes pollen sterility by interrupting tapetal programmed cell death (PCD). In this study, we demonstrated that overexpression of bHLH142 (OE142) under the control of ubiquitin promoter also leads to male sterility in rice by triggering the premature onset of PCD. Protein of bHLH142 was found to accumulate specifically in the OE142 anthers. Overexpr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…1A). Moreover, overexpressing bHLH142 caused premature upregulation of EAT1 (Ko et al, 2017). Third, TDR interacts with EAT1 (Ji et al, 2013;Ko et al, 2014;Niu et al, 2013) in regulating the expression of the downstream genes for pollen maturation.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…1A). Moreover, overexpressing bHLH142 caused premature upregulation of EAT1 (Ko et al, 2017). Third, TDR interacts with EAT1 (Ji et al, 2013;Ko et al, 2014;Niu et al, 2013) in regulating the expression of the downstream genes for pollen maturation.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, we have also shown that bHLH142 interacts with TDR to form a heterodimer and then co-modulate the expression of EAT1 expression (Ko et al, 2014). Moreover, overexpression of homologous bHLH142 leads to premature upregulation of EAT1 transcription and causes early tapetal PCD, suggesting that timely and precise control of bHLH142 level is critical to normal rice pollen development (Ko et al, 2017).…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation